Posłowie łęczyccy 1764-1792 i ich status majątkowy - Żerek-Kleszcz, Hanka (Acta Universitatis Lodziensis. Folia Historica, 2001)
The present article discusses results of the research into a number of Sejm deputies elected by the local electoral body in Łęczyca between the years 1764-1792. On the basis of the so-called lauds of these electoral bodies, it has been determined that during the above-mentioned period 15 local elections were held and those gave mandates to 33 people. A number of the elected deputies were given their functions many times. Financial status of those persons was determined upon the basis of a variety of documents showing purchase and selling transactions of the deputies’ properties and tax tables of the years 1775 and 1790. The electoral body in Łęczyca employed a high threshold of wealth in respect to the candidates. The deputies belonged to a narrow wealth elite of the region. Almost a half of them represented the financial status characteristic of only 1,2% of the entire noblemen’s population in the above-mentioned area.